LEGAL CERTAINTY ON BUILDING DISTRIBUTION AND CONFORMITY WITH THE DETAILED SPATING PLAN IN THE WILDLAND OF MENGWI SPECIFICALLY IN THE GREEN OPEN SPACE ZONE AND THE AGRICULTURAL ZONE (ANALYSIS OF LEGAL CERTAINTY FOR BUILDINGS THAT VIOLATE SPATIAL PLANNING) - Darmayanti, Ni Putu Eka; Wiratny, Ni Ketut; Sihotang, Erikson (International Journal of Social Service and Research, 2024)
This study aims to identify and understand in depth the factors that cause development in the green open space zone and agricultural zone in Mengwi District, Badung Regency, as well as analyze the legal certainty for building owners in these zones. The research was carried out in a qualitative descriptive manner with legal interpretation and legal communication methods, which systematically prepared legal materials to be presented in the thesis entitled "Legal Certainty Against the Distribution of Buildings and Conformity with Detailed Spatial Plans in the Mengwan District Area (RDTR WP), Especially in the Green Open Space Zone and Agricultural Zone." The results show that social factors such as population growth, inheritance rights distribution system, and low interest of the younger generation in agriculture are the most important factors that affect the development and conversion of green open spaces (RTH) in this area. However, there are challenges in law enforcement such as the effectiveness of long-standing regulations and the lack of public awareness of the importance of preserving green lanes. The government and related agencies need to be more decisive in sanctioning buildings in the area to maintain green areas and agriculture as a mitigation effort in preventing land conversion. This research is expected to be a guideline for the community in using land in accordance with spatial planning, providing input for the government on the legal impact of land use transitions, and providing guidance for all stakeholders related to land use.